A selective and mild glycosylation method of natural phenolic alcohols - Mastihubová, Mária; Poláková, Monika (Beilstein Journal of Organic Chemistry, 2016)
Several bioactive natural p-hydroxyphenylalkyl β-D-glucopyranosides, such as vanillyl β-D-glucopyranoside, salidroside and isoconiferin, and their glycosyl analogues were prepared by a simple reaction sequence. The highly efficient synthetic approach was achieved by utilizing acetylated glycosyl bromides as well as aromatic moieties and mild glycosylation promoters. The aglycones, p-O-acetylated arylalkyl alcohols, were prepared by the reduction of the corresponding acetylated aldehydes or acids. Various stereoselective 1,2-trans-O-glycosylation methods were studied, including the DDQ–iodine or ZnO–ZnCl2 catalyst combination. Among them, ZnO–iodine has been identified as a new glycosylation promoter and successfully applied to the stereoselective glycoside synthesis. The final products were obtained by conventional Zemplén deacetylation.
Keywords: diastereoselectivity; p-hydroxyphenylalkyl glycosides; mild promoters; natural products; 1,2-trans-glycosylation